Havening: a psycho-sensory therapy for enhancing emotional resilience and psycho-emotional wellbeing across the perinatal period - Susan Crowther; Christine Mellor; Kimm Sun (Frontiers in Global Women's Health, 2025)
Havening, a psycho-sensory therapy, is increasingly recognized for its potential in supporting perinatal psycho-spiritual and emotional health. By employing gentle touch and guided imagery, Havening aims to reduce distressing emotions and enhance well-being. This article explores its application on emotional processing in perinatal care, with a particular focus on its impact on the amygdala, the brain's emotional processing center. The theoretical foundations proposed by Dr. Ronald Ruden regarding Havening's neurobiological effects are discussed, followed by the presentation of four case studies and respective outcomes that demonstrate the potential of Havening in perinatal mental health.